Establishment of functional influenza virus-specific CD8+ T cell memory pools after intramuscular immunization. Issue 39 (22nd September 2015) - Wang, Zhongfang; Chua, Brendon Y.; Ramos, Javier Vega; Parra, Sergio M. Quiñones; Fairmaid, Emily; Brown, Lorena E.; Jackson, David C.; Kedzierska, Katherine
Abstract The emergence of the avian-origin influenza H7N9 virus and its pandemic potential has highlighted the ever-present need to develop vaccination approaches to induce cross-protective immunity. In this study, we examined the establishment of cross-reactive CD8+ T cell immunity in mice following immunization with live A/Puerto Rico/8/1934 (PR8; H1N1) influenza virus via two non-productive inoculation routes. We found that immunization via the intramuscular (IM) route established functional influenza-virus specific memory CD8+ T cell pools capable of cross-reactive recall responses. Epitope-specific primary, memory and recall CD8+ T-cell responses induced by the IM route, highly relevant to human influenza immunisations, were of comparable magnitude and quality to those elicited by the intraperitoneal (IP) priming, commonly used in mice. Furthermore, IM immunisation resulted in lower lung viral titres following heterologous challenge with A/Aichi/68 (X31; H3N2) compared to the IP route. Examining the ability of DCs from lymphoid organs to present viral antigen revealed that immune induction following IM immunization occurred in draining lymph nodes, while immunization via the IP route resulted in the priming of responses in distal lymphoid organs, indicative of a systemic distribution of antigen. No major differences in the pulmonary cytokine environment of immunized animals following X31 challenge were observed that could account for the improved heterologous protection induced by the IM route. However, while both routes induced similar levels of PR8-specific antibodies, higher levels of cross-reactive antibodies against X31 were induced following IM inoculation. Our data demonstrate how non-replicative routes of infection can induce efficient cross-reactive CD8+ T cell responses and strong strain-specific antibody responses, with the additional benefit from IM priming of enhanced heterosubtypic antibody production.